2011
DOI: 10.1590/s0100-69912011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Influência da dieta com galactooligossacarídeos sobre a absorção de cálcio em ratos normais e gastrectomizados

Abstract: The ingestion of galactooligosaccharides prevents osteopenia in partially gastrectomized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Ohta and colleagues confirmed that dietary FOS enhanced Mg absorption and the absorption of Ca, Mg and Fe in Mg-deficient rats and Fe-deficient anemic rats respectively [ 112 , 113 ]. As well, dietary supplements of GOS, FOS, DFA III, polydextrose and epilactose were reported to increase Ca and Fe bioavailability and prevent anemia in gastrectomized animal models [ 111 , 114 , 115 , 116 , 117 ].…”
Section: Effects On Nutrient Digestion Absorption and Systemic Mmentioning
confidence: 99%
“…Ohta and colleagues confirmed that dietary FOS enhanced Mg absorption and the absorption of Ca, Mg and Fe in Mg-deficient rats and Fe-deficient anemic rats respectively [ 112 , 113 ]. As well, dietary supplements of GOS, FOS, DFA III, polydextrose and epilactose were reported to increase Ca and Fe bioavailability and prevent anemia in gastrectomized animal models [ 111 , 114 , 115 , 116 , 117 ].…”
Section: Effects On Nutrient Digestion Absorption and Systemic Mmentioning
confidence: 99%
“…De acordo com Pond e Maner (1974) apud Miyada 22 , os níveis de hemoglobina e hematócrito são indicativos do estado nutricional dos suínos quanto ao ferro. Embora trabalhando com prebióticos diferentes dos avaliados no presente trabalho, Santos 23 observou que a suplementação das dietas com galactooligossacarídeo e polidextrose, aumentou não apenas o ferro sérico de ratos, mas também as concentrações de hemoglobina e hematócrito, sugerindo que os prebióticos têm efeito potencializador na absorção de ferro. Por outro lado, para as características de leucograma, observou-se que a adição de MOS nas dietas não promoveu alterações nos números de linfócitos e neutrófilos nos leitões.…”
Section: Resultsunclassified
“…Vários relatos sugerem também que os GOS, dentre outros carboidratos não digeríveis, estimulam e aumentam a absorção de cálcio e minerais no intestino. Este efeito consiste na produção de ácidos graxos de cadeia curta, resultante da fermentação no intestino grosso, uma vez que eles estimulam a proliferação de células do epitélio do intestino e reduzem o pH luminal (Rastall, 2013;Santos et al, 2011;Scholz-Ahrens et al, 2007).…”
Section: Efeitos Benéficos à Saúdeunclassified